2007
DOI: 10.1523/jneurosci.4383-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Homeostasis of Mouse Retinocollicular Synapses

Abstract: ) that lack correlated waves, retinocollicular map refinement is impaired. In vivo recordings reveal that neurons in the superior colliculus of ␤2 Ϫ/Ϫ mice have large receptive fields and low peak visual responses, resulting in a conservation of total integrated response. We find that this "response homeostasis" is maintained on a cell-bycell basis, and argue that it does not depend on regulation from the visual cortex during adulthood. Instead, in vitro recordings show that homeostasis arises from the conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 51 publications
9
90
2
2
Order By: Relevance
“…Similar observations have been made in immature visual cortex, where mEPSC frequency is inversely correlated with amplitude (Desai et al, 2002), and in the superior colliculus, where RGC inputs are weak in neurons that receive input from a large number of RGCs, whereas RGC inputs are stronger in neurons receiving input from few RGCs (Chandrasekaran et al, 2007). This observation suggests that EPSC amplitude is not necessarily the best indicator of total synaptic drive, because we see a developmental increase in total synaptic drive despite a decrease in sEPSC amplitude.…”
Section: Maturation Of Synaptic Transmissionsupporting
confidence: 79%
“…Similar observations have been made in immature visual cortex, where mEPSC frequency is inversely correlated with amplitude (Desai et al, 2002), and in the superior colliculus, where RGC inputs are weak in neurons that receive input from a large number of RGCs, whereas RGC inputs are stronger in neurons receiving input from few RGCs (Chandrasekaran et al, 2007). This observation suggests that EPSC amplitude is not necessarily the best indicator of total synaptic drive, because we see a developmental increase in total synaptic drive despite a decrease in sEPSC amplitude.…”
Section: Maturation Of Synaptic Transmissionsupporting
confidence: 79%
“…This supports the hypothesis that synaptic competition stabilizes developing axons and eliminates inappropriate connections in mammals as well. We previously showed that ␤2 Ϫ/Ϫ synapses at P6 -P7 are not only weaker but also greater in number relative to control synapses (Chandrasekaran et al, 2007). Correlated presynaptic activity, therefore, may be the necessary upstream signal for synaptic learning rules to strengthen appropriate synapses and eliminate inappropriate inputs.…”
Section: Model Of Synaptic-competition-based Retinotopic Map Refinementmentioning
confidence: 98%
“…Number of cells is written adjacent to each group. P6 -P7 data points come from Chandrasekaran et al (2007). In control synapses, there is a developmental increase in AMPA/NMDA ratios from P3-P4 to P6 -P7 (**p Ͻ 0.01).…”
Section: Development Of Ampa Miniature Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Homeostatic plasticity is critical for maintaining stability in neuronal networks involved in various physiological processes, including neurodevelopment (Chandrasekaran et al, 2007) and learning and memory (Nelson and Turrigiano, 2008). In response to changes in synaptic strength, homeostatic plasticity reestablishes a fine balance between excitation and inhibition.…”
Section: Introductionmentioning
confidence: 99%